(untitled) (International Journal of Innovative Technologies in Economy, 2023)
Digital Financial Services (DFS) present an opportunity to expand financial access within society; however, DFS adoption remains relatively low in Indonesia. This study aims to assess how individual perceptions of internet connection quality and the credibility of DFS platforms influence their adoption in Indonesia. Utilizing data from the 2020 Digital Economy Household Survey (DEHS) and employing the probit and ordered probit estimation models, the research demonstrates a positive and significant relationship between perceptions of internet connection quality, DFS platform credibility, and the likelihood and frequency of DFS usage. Notably, a majority of DFS users fall under the "occasionally used" category, indicating usage ranging from 3 to 30 minutes per day. The study underscores the need for collaborative efforts to establish a well-distributed, trusted, and secure DFS ecosystem. This necessitates addressing regulatory frameworks, enhancing infrastructure, and improving public financial literacy to enhance user acceptance and utilization of DFS platforms.